Internalisasi Nilai Moderasi Beragama Melalui Kegiatan Sadranan Di Desa Jubelan - Tisa Valentina; Syarif Abdul Aziz (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to analyze the internalization of the value of religious moderation through religious activities in Jubelan Village. This type of research is qualitative with a case study approach. This approach involves an in-depth analysis of one or several cases that represent concrete examples of the phenomenon being studied. Data were collected using observation, interviews with community experts, Jubelan village government figures and religious leaders. Data analysis using mile Huberman analysis with data reduction, data display and conclusions. Sadranan activities in Jubelan Village are an important means of internalizing the value of religious moderation, strengthening solidarity between residents, and maintaining social harmony. Through awareness, the people of Jubelan Village work together to instill religious values in their daily lives, such as tolerance, togetherness and willingness to help others. This creates an inclusive environment and strengthens the sense of brotherhood between them, as well as strengthening identity and pride in the religious values they adhere to. In this way, meditation in Jubelan Village is not only a routine event, but also an effective vehicle for forming moderate religious character and attitudes in the community.